An intergenerational program based on psycho-motor activity promotes well-being and interaction between preschool children and older adults: results of a process and outcome evaluation study in Austria - Erika Mosor; Karin Waldherr; Ingvild Kjeken; Maisa Omara; Valentin Ritschl; Veronika Pinter-Theiss; Josef Smolen; Ursula Hübel; Tanja Stamm (BMC, 2019)
Abstract Background Limited evidence exists for intergenerational interventions to promote health and well-being in older adults and preschool children. We therefore aimed to evaluate the implementation, feasibility and outcome of an intergenerational health promotion program based on psycho-motor activity. Methods A multicenter mixed-methods study with preschool children and older adults as equivalent target-groups, and professionals and parents as additional informants was conducted in Austria. The study included a needs assessment, a pilot phase with a formative process evaluation and a subsequent rollout phase to evaluate the outcome and the adapted processes of the intervention program. To analyze the qualitative data, a modified form of the framework method was applied. Quantitative data were collected with a time-sampling method and were analyzed using descriptive and inferential statistical procedures. Results One hundred ninety-six participants (93 older adults [54 to 96 years old, 83% female], 78 children [2 to 7 years old, 58% female], 13 professionals and 12 parents) from 16 institutions (eight kindergartens and eight geriatric facilities) were included in the study. The qualitative process evaluation revealed several aspects for improvement of the intervention program. Well-being as measured by observing spontaneous intergenerational contacts (p < 0.001) and facial expressions (effect size r = 0.34; p < 0.001) showed a significant increase between the rollout baseline and follow-up assessments. Conclusions Professionals in geriatric institutions and kindergartens could facilitate interactions between members of the different generations by offering an intergenerational intervention program based on psycho-motor activities in the future.